Oral Hygiene in Children with Autism: Teaching Self-Toothbrushing via Behavioural Intervention Including Parents - Marco Esposito; Carlotta Piersanti; Roberta Fadda; Marco Boitani; Monica Mazza; Giuseppina Marrocco (Children)
Background/Objectives: Children on the autism spectrum experience more oral hygiene issues than peers, and tooth-brushing behavior seems particularly challenging for them since it includes diverse skills and collaboration. In this study, the efficacy is explored of a behavioral intervention mediated by staff and parents in teaching self-brushing teeth in eight autistic children. First, we wanted to examine whether the intervention improved self-brushing teeth skills in a short-term period. Second, we evaluated the long-term outcomes of the intervention. Finally, we analyzed the individual differences which might predict better outcomes. Methods: The training started during an ABA summer school with a supervised behavioral staff and lasted for eight sessions. The training package included several behavioral procedures such as prompting, fading, task analysis, chaining, differential reinforcement, direct instructions, visual aids, pictograms, and video modeling. According to a pre-and post-test design, we measured the frequency of independent self-brushing behaviors and interviewed the parents about the hygiene routines. Results: The results indicate a significant improvement in children’s self-brushing teeth behavior and maintenance, where 33.7% of the steps were achieved by children at baseline and 77.5% at post-training, and with four children, 100%. The parent questionnaires reported significant improvement in autonomy of self-brushing and times a day dedicated to oral hygiene. The severity of symptoms, sensory hypersensitivity, and lower IQ levels of the children negatively correlated with the outcome. Conclusions: These results point to relevant practical suggestions for families and clinical staff to address oral hygiene in the autism population.